Catering through Nominal Share Prices - BAKER, MALCOLM; GREENWOOD, ROBIN; WURGLER, JEFFREY (Journal of Finance, 2009)
ABSTRACT We propose and test a catering theory of nominal stock prices. The theory predicts that when investors place higher valuations on low‐price firms, managers respond by supplying shares at lower price levels, and vice versa. We confirm these predictions in time‐series and firm‐level data using several measures of time‐varying catering incentives. More generally, the results provide unusually clean evidence that catering influences corporate decisions, because the process of targeting nominal share prices is not well explained by alternative theories.